Comparison of the Effectiveness of Emotion Regulation Training and Mindfulness Skills Training on Reducing Traditional and Cyber Bullying Among High School Students in Tehran - Yazdani Sarijeh, Fereshteh; Yousefi, Emad; Khajeh Pour, Leila (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: Academic problems affect students' performance inside and outside the learning environment. Therefore, it is necessary to employ interventions based on novel and tested methods. This study examines the "effectiveness of emotion regulation training and mindfulness skills training on reducing traditional and cyberbullying among high school students in Tehran." Methods: The present study is a quasi-experimental research with a pretest-posttest and follow-up design with a control group. The statistical population consisted of high school students in Tehran, and the sampling method was multi-stage cluster sampling. Two schools and 45 students were randomly selected as the research sample. They were randomly assigned to three groups of 15. The data obtained through the questionnaire were analyzed using SPSS 25 software. Results: During the emotion regulation training period, there was a significant difference between the pretest and posttest mean scores of traditional bullying, and the pretest and posttest mean scores of cyberbullying. Additionally, during the mindfulness training period, the pretest mean scores of traditional bullying showed a significant reduction in the posttest, as did the pretest mean scores of cyberbullying. In the control group, there was no significant difference between the pretest mean score of traditional bullying (90.07) and the posttest, nor between the pretest mean score (40.07) and the posttest of cyberbullying. Conclusion: The results showed that emotion regulation skills and mindfulness were effective in reducing traditional and cyberbullying among students, with no significant difference between the impact of emotion regulation and mindfulness on traditional bullying. Mindfulness training reduces violence in students. Mindful individuals possess problem-solving skills, actively seek methods to solve their problems, monitor them, and better overcome situational obstacles and problems in life. Therefore, violence is a characteristic of individuals with low mindfulness and emotion regulation who lack problem-solving skills.